2005
DOI: 10.1111/j.1526-4610.2005.05029.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Venlafaxine in the Prophylaxis of Migraine

Abstract: Venlafaxine was more effective than placebo and is safe and well tolerated as migraine prophylaxis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(117 citation statements)
references
References 28 publications
2
104
0
11
Order By: Relevance
“…AEs include increased appetite, weight gain, dry mouth and sedation; cardiac toxicity and orthostatic hypotension occasionally occur. Selective 5-HT reuptake inhibitors (SSRIs) are probably not effective at preventing migraine, whereas the results of open and smaller studies indicate that selective norepinephrinereuptake inhibitors (SNRIs) are effective [19]. The mechanism by which antidepressants prevent headache is unclear but it does not result from treating masked depression.…”
Section: Antidepressantsmentioning
confidence: 97%
“…AEs include increased appetite, weight gain, dry mouth and sedation; cardiac toxicity and orthostatic hypotension occasionally occur. Selective 5-HT reuptake inhibitors (SSRIs) are probably not effective at preventing migraine, whereas the results of open and smaller studies indicate that selective norepinephrinereuptake inhibitors (SNRIs) are effective [19]. The mechanism by which antidepressants prevent headache is unclear but it does not result from treating masked depression.…”
Section: Antidepressantsmentioning
confidence: 97%
“…The results of the study indicated that venlafaxine was more effective compared to placebo in migraine prophylaxis and considered a well-tolerated drug. [12] In another study conducted to investigate the effectiveness of venlafaxine and amitriptyline in migraine prophylaxis, both were found to be significantly effective in reducing pain parameters but the side effect profile of venlafaxine was found superior when compared to that of amitriptyline. [13] Similar to the results of this study, our study recorded a decrease in pain intensity, frequency and duration after venlafaxine intake (75-225 mg/day).…”
Section: Discussionmentioning
confidence: 99%
“…Trials of venlafaxine have shown that a 150-mg dosage is superior to placebo 34 for prevention of migraine, with a median reduction of four days with migraine in the last two weeks of therapy compared to the first two weeks. Antidepressants should be considered for prophylaxis of migraine in patients with a coexisting anxiety or mood disorder.…”
Section: Antidepressantsmentioning
confidence: 99%